Health Promoting Lifestyle Behaviors and Sleep Quality Among Saudi Postmenopausal Women - Enas Mahrous Abdelaziz; Enas Mahrous Abdelaziz; Nadia Bassuoni Elsharkawy; Nadia Bassuoni Elsharkawy; Sayeda Mohamed Mohamed (Frontiers Media S.A., 2022)
BackgroundOne of the most effective measures regarding improving women's health is to promote healthy lifestyle behaviors. This study aimed to investigate the relationship between health-promoting behaviors and sleep quality among a sample of Saudi menopausal women.MethodsA descriptive cross-sectional study was used to collect data from 410 Saudi postmenopausal women visiting primary healthcare care centers located in Sakaka, Jouf, Saudi Arabia, using the Menopause Rating Scale (MRS), Health-Promoting Lifestyle Profile II (HPLPII) and Pittsburgh Sleep Quality Index (PSQI).ResultsThe mean age of the study participants was 52.60 ± 4.65 years, the study findings highlighted that among all the HPLP domains, the highest mean score was observed for spiritual growth (24.00 ± 6.60) whereas the lowest score was observed for physical activity (16.18 ± 1.8). Statistically significant negative relations between the total score of HPLP and sleep quality score and menopausal symptoms (p < 0.001, p < 0.005), respectively. Total scores of lifestyle, health responsibility, and stress management were significant differences between participants with good and poor sleep quality. Being overweight/obese, physically inactive, having a chronic illness and poor sleep quality were predictors influencing health-promoting behavior.ConclusionHealth-Promoting Lifestyle Profile II was more obvious in the good sleeper in form of health responsibility and stress management. Being overweight and or obese, having a chronic illness, and having poor sleep quality were the significant factors influencing health-promoting behaviors. Designing and performing educational interventional plans are crucial to create motivation toward a healthy lifestyle and improve the quality of their sleep.